View of social educators on the educational work performed in STD/aids prevention - Ana Débora Assis Moura; Ana Karina Bezerra Pinheiro; Maria Grasiela Teixeira Barroso (Rev Rene)
This study aims to outline a socio-demographic profile of the social educators (SE) of the Association of Prostitutes of the state of Ceará (APROCE) and to investigate these women’s view on the educational work done in STD and AIDS prevention. This is a descriptive research with qualitative approach. The data were collected from November 2006 to January 2007, following the SE to some prostitution areas of Fortaleza. The data were classified in two categories: characterization of the social educators and dialogue with the social educators which were analyzed, according the critical analysis. It was verified that the health education strategies used by APROCE don’t stimulate change of behavior, because a lot of prostitutes still have sexual intercourse without using condom. Although APROCE releases information on STS/AIDS prevention and give condoms, the strategies used by the association should be improved in order to promote self-criticism on the adopted behavior.